Prevalence of basilar artery variants: a systematic review with meta-analysis of radiological studies. - Triantafyllou, George; Paschopoulos, Ioannis; Papadopoulos-Manolarakis, Panagiotis; Arkoudis, Nikolaos-Achilleas; Velonakis, Georgios; Papanagiotou, Panagiotis; Piagkou, Maria (Neuroradiology, 2026)
Purposes: To provide a comprehensive meta-analytic synthesis of the morphological variability of the basilar artery (BA) - specifically fenestrations, persistent trigeminal arteries (PTA), and aberrant posterior inferior cerebellar artery (PICA) origin - and to elucidate their clinical implications for neuroradiological and neurosurgical procedures. Methods: Following PRISMA 2020 and Evidence-Based Anatomy guidelines, a systematic literature search of three databases was performed. Inclusion criteria focused on imaging studies (CTA, MRA, DSA) reporting the prevalence of specific BA variants. Pooled prevalence was calculated using random-effects models via R programming software. Results: Thirty-five studies involving 266,696 patients were included. The aberrant PICA origin from the BA was the most frequent variant, with a pooled prevalence of 4.53% (95% CI: 0.06–14.52). BA fenestration followed with a prevalence of 1.36% (95% CI: 0.93–1.86), showing a statistically significant difference in detection between MRA (1.69%) and DSA (0.24%). The rarest variant was the PTA, calculated at 0.20% (95% CI: 0.11–0.31). Considerable heterogeneity was observed across pooled estimates. Conclusions: Although BA variations are relatively infrequent, their precise identification is a clinical necessity for procedural safety. Awareness of these variants is vital for navigating complex vascular geometries and managing the potential risk of associated aneurysms during endovascular interventions.